The Petterns Of Drug Use During Self-Isolation By Confirmed COVID-19 Patients at the Asam Baru Health Center: Pola Penggunaan Obat Selama Isolasi Mandiri Oleh Pasien Terkonfirmasi COVID-19 di Puskesmas Asam Baru - Jumiyatul Awlia, Siti (Jurnal Farmasi Ma Chung: Sains, Teknologi, dan Klinis Komunitas, 2024)
Patients who are confirmed with COVID-19 with asymptomatic conditions with asymptomatic and mild conditions undergo isolation and monitoring with pharmacological treatment of vitamin C, vitamin D, supportive medicines both traditional and conventional and antivirals for mild conditions. This study aims to determine the pattern of drug use during self-isolation by confirmed COVID-19 patients at the Asam Baru Health Center for the January-July 2022 period, the relationship between the acquisition of therapy from health services with the effectiveness of therapy, and the relationship between the effectiveness of therapy and patient characteristics. The design of this study is observational with cross-sectional methods and retrospective data collection. The data obtained will be presented descriptively in the form of percentages as well as statistical analysis. The pattern of drug use during self-isolation by confirmed COVID-19 patients was vitamin C 56%, vitamin D 11.11%, and zinc 19.44%, azithromicyn 100% from 3 respondents, oseltamivir as much as 89% and favipirapir 11%, paracetamol 500mg 53%, cough medicine and sputum thinner 29%, and dexamethasone 0.5mg 18%. Traditional medicine is 60% ginger steeping and 40% temulawak steeping. There was no association between therapeutic gains from health services and therapeutic effectiveness with a significant value of 0.332. There is a significant relationship between the effectiveness of patient therapy and the patient's age with a significant value of 0.000. There was no significant relationship between the effectiveness of therapy with comorbid patient value 0.233, patient sex value 0.854, and vaccination in patients value 0.723.